PENDIDIKAN KESEHATAN KELUARGA TENTANG MANFAAT IMUNISASI BACILLUS CALMETTE GUERIN (BCG) PADA BAYI USIA 0-12 BULAN DI UPT PUSKESMAS MEDAN DELI - Fakhiru Rizka; Ade Irma Khairani; Resmi Pangaribuan (SINERGI : Jurnal Riset Ilmiah, 2026)
Health education is an effort to deliver health information to individuals or communities with the aim of improving their knowledge regarding health. One of the mandatory basic immunizations is the Bacillus Calmette—Guérin (BCG) vaccine, which serves to prevent tuberculosis. Based on information gathered in the community, there remains a lack of uniform understanding regarding immunization, resulting in many infants not receiving immunization services. This study aims to apply family nursing care by providing health education on the benefits of BCG imntunizationfor infants aged 0—12 months in the working area of Medan Deli Community Health Center. The research employed a descriptive method with a case study approach, involving two families with infants aged 0—12 months. Data were collected through interviews, observations, and the delivery of health education using leaflets. The intervention was carried out to improve family knowledge regarding the benefits of BCG immunization as well as the importance of completing basic immunizations for infants. The results showed that prior to receiving health education, the families ' level ofknowledge was low, and there were concerns about the side effects of immunization. After the health education was provided, there was an increase in family understanding of the benefits of BCG immunization. Families also demonstrated positive changes in attitude toward the implementation of health education delivered to them. Conclusion: Health education is effective in improving family knowledge regarding the benefits of BCG immunization. It is expected that healthcare workers continue to provide consistent and ongoing education to ensure adequate immunization coverage in the community